Aktivitas Antioksidan, Kadar Glukosa Dan OrganoleptikMinuman Instan Daun Binahong (Anredera cordifolia)Dengan Variasi Pemanis Alami - Umikasih, Siti; , Dra. Titik Suryani, M.Sc (2015)
Beverage instan is one of the traditional herbal beverage processed products are soluble in water, practically in the presentation and have a longer shelf life because the water level is low and has a large surface area. Binahong contains terpenoids, saponins, phenols, volatile oils and flavonoids are efficacious for various diseases one diabetes mellitus. Leaf ethanol extract has antioxidant binahong 4.25 mmol / 100g (fresh) and 3.68 mmol / 100g (dry). The purpose of this study to determine the antioxidant activity and glucose levels instant powder drink with variations binahong leaf natural sweetener. The design of this study with a completely randomized design 2 factors: factor 1: Leaves binahong 50g (P1); binahong leaves 60g (P2); binahong leaves 70g (P3) and factor 2: White sugar 50g (L1); rock sugar 50g (L2). Results showed that the highest antioxidant binahong leaves 60g to 50g of rock sugar, high glucose levels in the leaves binahong 50g to 50g of sugar cubes while antioxidants and low glucose levels in the leaves binahong 50g sugar 50g. Organoleptic powder drink green leaves dominant, distinctive aroma, and has a sweet taste, while the panelists received power at binahong leaves with the addition of 50g sugar 50g.